Modeling of Three Crossroad Traffic Flow Queuing Systems Using Max-Plus Algebra - Margaretha Nobilio Pasia Janu (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2019)
This study aims to determine the model of the traffic flow queuing system of three crossroads, that is the Monjali, Kentungan, and Gejayan crossroad in Yogyakarta using max-plus algebra. This research is based on data on traffic flow density, especially cars and traffic light duration data on the three crossroads. Then, an image is drawn describing the condition of the crossroad and representing the direction of the movement of the car especially in the direction of Monjali to Gejayan. The model is then compiled which includes the waiting time of the car when the red lights are on, the time the car leaves the crossroad during the green light, and the travel time of the vehicle crossroad with max-plus algebra, so that the total length of time from Monjali to the Gejayan crossroad can be determined. The results of the study show that the queue system can be modeled using max-plus algebra. Furthermore, it can be determined the waiting time, the time to leave the intersection, and the total time needed to cross from the Monjali to exit at Gejayan.